Interfacial modulation achieving a flexible anode of FeP/N-doped C@carbon cloth with a robust structure for high areal capacity lithium storage. Issue 20 (22nd September 2021) - Wang, Weijuan; Xu, Hui; Yu, Genxi; Chen, Daming; Sun, Shangqi; Zhou, Min; Chen, Jian
Abstract : This proposed interfacial strategy with significant capability in improving the mass loading of active materials can benefit the development of high areal capacity flexible electrodes. Abstract : Rationally engineering flexible anodes with electrochemical and mechanical robustness while maintaining structural integrity is highly desirable for the realization of high-performance flexible lithium-ion batteries (LIBs). Herein, an integrated flexible anode composed of porous FeP nanocrystals/N-doped C frameworks and a conductive carbon cloth skeleton (FeP/NC@CC) that is constructed using amine-functionalized Fe-MOFs as precursors to achieve efficient interfacial modulation is reported. The FeP/NC frameworks derived from the Fe-MOFs can anchor firmly on the acidized CC skeleton, avoiding shedding of active materials with a high mass loading. The FeP nanocrystals embedded in the NC frameworks not only improve their electrical conductivity, but also form a stable solid electrolyte interphase (SEI) layer on the anode surface to prevent structural degradation and unfavorable side reactions for high cycling efficiency. In addition, the porous structure can facilitate electrolyte penetration and effectively accommodate mechanical strain from the volume change of FeP. Benefiting from the unique structure, FeP/NC@CC delivers a reversible areal capacity (5.8 mA h cm −2 at 0.15 mA cm −2 ) with a high initial coulombic efficiency of 80.5% and excellent rate capability (2.0 mA h cm −2 at 6.0 mA cm −2 ). The full cell composed of FeP/NC@CC and LiFePO4 also shows good cycling stability.